Dimensions of Individual, Occupational, and Organizational Characteristics on the Performance - Tehubijuluw Zacharias (Jurnal Manajemen Pelayanan Publik, 2024)
This research examines the influence of individual, job, and organizational characteristics on employee performance. The study utilizes a descriptive-quantitative approach with a cause-and-effect correlation type. The research spans over two months and involves all 44 Central Maluku Regency Fisheries Service employees. The sample is chosen using complete sampling, and data is analyzed through multiple linear regression analysis. The research findings indicate that job characteristics also have a significant and positive impact on employee performance, individual characteristics have a significant and positive effect on employee performance, organizational characteristics significantly and positively influence employee performance, and overall, personal, job, and organizational characteristics collectively have a significant and positive influence on employee performance. Job characteristics and organizational characteristics have a positive and significant effect on employee performance.